Channel coordination with quantity discounts and/or cooperative advertising. Issue 17 (1st September 2016) - Karray, Salma; Surti, Chirag
Abstract : We assess the interactive effects of two commonly used channel coordination mechanisms (quantity discounts (QDs) and cooperative advertising (CA)). We use a game-theoretic model and solve four non-cooperative games. In the first game, neither QDs nor CA is implemented. Cooperative advertising alone is offered in the second game, while quantity discounts alone are offered in the third game. In the fourth game, both QDs and CA are implemented. We obtain analytical solutions and compare equilibrium results across games to assess the effectiveness of CA (QDs) when implemented alone or jointly with QDs (CA). The main findings suggest that the profitability of each of these mechanisms is affected by whether the other is implemented or not in the channel. For example, while CA benefits the manufacturer when implemented alone, it can increase or decrease the manufacturer's profit when added to QDs. Looking at which coordination mechanism is most effective when used alone, we find that both the manufacturer and the supply chain prefer QDs to CA. Finally, the retailer may not benefit from either one or both of these coordination mechanisms, especially if marketing efforts are not highly effective.